2021
DOI: 10.1016/j.redox.2021.102128
|View full text |Cite
|
Sign up to set email alerts
|

TMBIM6 regulates redox-associated posttranslational modifications of IRE1α and ER stress response failure in aging mice and humans

Abstract: Age-associated persistent ER stress is the result of declining chaperone systems of the ER that reduces cellular functions, induces apoptosis, and leads to age-related diseases. This study investigated the previously unknown regulatory mechanism of TMBIM6 during age-associated hepatic abnormalities. Wild-type (WT) and the TMBIM6 knockout (TMBIM6 −/− ) mice liver, human liver samples from different age groups were used to demonstrate the effect of physiological aging on liver. For TMBIM6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…In obesity showing ER stress conditions, we asserted that obesity-induced and phosphorylation-independent modifications in IRE1α might suppress ribonuclease activity selectively. We observed a substantial rise in iNOS expression in HFD conditions, which coincides with the decrease in the sXBP1 activity “the nuclear translocation of sXBP-1” in adipose tissue of obese mice ( Figure 3 f) [ 16 ]. This coincidence represents an obesity model featuring chronic metabolic inflammation [ 21 , 22 , 23 ], whereas IBF-R significantly suppressed the iNOS level.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…In obesity showing ER stress conditions, we asserted that obesity-induced and phosphorylation-independent modifications in IRE1α might suppress ribonuclease activity selectively. We observed a substantial rise in iNOS expression in HFD conditions, which coincides with the decrease in the sXBP1 activity “the nuclear translocation of sXBP-1” in adipose tissue of obese mice ( Figure 3 f) [ 16 ]. This coincidence represents an obesity model featuring chronic metabolic inflammation [ 21 , 22 , 23 ], whereas IBF-R significantly suppressed the iNOS level.…”
Section: Resultsmentioning
confidence: 97%
“…IBF-R demonstrated its potentials in regulating adipogenesis by sustaining redox-linked PTMs and ER homeostasis. Moreover, previously, we have demonstrated that severe redox-mediated PTMs of IRE1α impairs ER function and sustain ER stress in aging/metabolic disorder models suggesting the S-nitrosylation of IRE1α affects its endoribonuclease activity, thereby impairs sXBP1, leading to inflammation [ 16 ]. In addition, the increased iNOS-induced metaflammation is associated with impaired XBP1 processing in obesity [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that TMBIM6 is essential for ER homeostasis (Lebeaupin et al 2020 ; Bhattarai et al 2021 ). The m 6 A sites of TMBIM6 were predicted using two databases, RMBase v2.0 ( http://rna.sysu.edu.cn/rmbase/ ) and M6A2Target ( http://m6a2target.canceromics.org/ ) (Deng et al 2021 ; Xuan et al 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…The transmembrane Bax inhibitor motif containing 6 (TMBIM6), also known as Bax interactivator-1 (BI-1), is a highly conserved transmembrane protein primarily located in the ER (Lebeaupin et al 2020 ). TMBIM6 inhibits Bax-induced apoptosis, shows beneficial effects against ER stress and calcium imbalance, and possesses anti-inflammatory and anti-oxidative properties (Lebeaupin et al 2020 ; Han et al 2021 ; Bhattarai et al 2021 ). TMBIM6 can inhibit ER stress-induced apoptosis via multiple mechanisms, such as by regulating the calcium flux in the ER lumen, activating the PERK/ATF4/CHOP pathway, and limiting reactive oxygen species (ROS) production (Lebeaupin et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%